Phenolic lipid derived coordination polymer nanocomposites: Synthesis, characterization and surface protective coating applications - Shabnam Khan; Shaily; Anujit Ghosal; Shahnawaz Ahmad Bhat; Fahmina Zafar; Mudsser Azam; Manawwer Alam; M. Shahid; Qazi Mohd Rizwanul Haq; Nahid Nishat (Applied Surface Science Advances, 2022)
Fabrication of renewable-resource (Cardanol, Col) based nanocomposite films/coatings has opened up a new path in the development of a sustainable and environment-friendly polymeric material with prodigious attention. In the present work, Co(II) and Ni(II) coordinated Col nanocomposites (Col-CPU/CoO and Col-CPU/NiO) have been fabricated via following an easy, cost-effective, in-situ approach. These materials have been used to develop mechanically robust, anti-corrosive, antibacterial thin films and coatings against gram-positive (S.aureus and B.subtilis) and gram-negative (E.coli and P.aeruginosa) bacteria. Spectral techniques were used to deduce the mode of formation and geometry of synthesized nanocomposites. The prepared nanocomposites of Co(II) and Ni(II) demonstrate improved thermal stability and flame retardant behavior with the aid of metal nodes compared to the pristine polymer. The developed films displayed amorphous behavior with a layered pattern and nano-porous morphology over the surface of the nanocomposites which was confirmed by the Brunauer-Emmett-Teller (BET) studies. Surface wettability studies revealed hydrophobic and superhydrophobic surfaces with a contact angle of 143° of Col-CPU/CoO and 158° of Col-CPU/NiO, respectively. Superior physicomechanical properties of metal nanocomposites such as scratch hardness, crosshatch, gloss, bend test, and impact resistance, compared with the pristine polymer point to a uniform distribution of metal-coordinated networks. Therefore, this cost-effective and sustainable approach can be utilized for the development of polyurethane (PU) nanocomposites that could be employed as thermally stable, fire-retardant, anti-corrosive, antibacterial films and coatings in different fields of applications.